A Systematic Review of Traceability and Monitoring in Port Transportation Processes for Halal Compliance and Certification - Yaacob, Teh Zaharah; Majid, Mazlinawati Abdul; Hashim, Hanini Ilyana Che; Hasan, Mohd Zulfabli (Journal of Accounting, Business and Management (JABM), 2024)
This systematic review provides a comprehensive analysis of halal transportation practices at ports, with a focus on the critical aspects of traceability and monitoring mechanisms. As the global halal market continues to expand rapidly, ensuring the integrity of halal products across the entire supply chain, particularly during port clearance and transportation—has become increasingly vital. This article synthesizes current research on the challenges faced in transportation, technological advancements, and the regulatory frameworks governing halal logistics at ports. It evaluates existing methods for tracking and verifying the halal status of goods from their origin to the destination, emphasizing the pivotal role of traceability and monitoring in upholding halal integrity. The review identifies significant gaps in the literature, particularly concerning the standardization of halal transport protocols and the integration of advanced tracking technologies. Additionally, it examines the policies and regulatory bodies responsible for overseeing the halal transport process. The findings underscore the urgent need to develop comprehensive, globally recognized guidelines that can adapt to the rapidly evolving technological landscape and address the diverse needs of the halal market. This study is instrumental in fostering more efficient, transparent, and reliable halal shipping practices at ports, ultimately bolstering consumer confidence and supporting the continued growth of the global halal market.